Optimizing economic potentials of sustainable agriculture and eco-tourism amongst Orang Sungai community: technology transfer to Koperasi Pelancongan Mukim Batu Puteh (KOPEL), Kinabatangan, Sabah - Connie Fay Komilus; Bonaventure Boniface; Markus Atong; Jupikely James Silip (2015)
This paper presents the progress of activities of knowledge transfer programme (KTP} that were carried out by a group of academia from UMS, UniSZA and UniMAP in KOPEL, Kinabatangan until May 2015. This project co,•ers a two year programme (April 2014 - April 2016) and aims to optimize income of KOPEL 's community via sustainable agriculture concept, adopting environmental stewardship, economic feasibility and social well-being. KOPEL is a community-based cooperative located at Kinabatangan District in the east coast of the State of Sabah, Malaysia. The district lies within the Eastern Sabah Security Zone (ESSZONE). Much of KOPEL 's income (approximately 96%) comes from foreign tourists. Due to the terrorist crisis which occurred in the eastern part of Sabah from February to May 2013, KOPEL 's business operations, such as .. homestay and tourism activities, had been greatly affected. There were altogether five training modules successfi11/y exte11ded to about 60 members of KOPEL comprising i. Entomology for Tourism (KK.10103), ii. Business Administration and Economic Management (KK10203}, iii. Fertigation Technology and Post-Harvest Management (KKJ0303), iv. Aquaculture Technology (KK10403), and v. Downstream Processing Technology and Food Sen1ices (KK10503). Much of the success in the KTP-KOPEL project was greatly attributable to the role of Graduate Intern (GI) in managing the KTP activities, such as, the arrangement of the learning session modules for communities, setting up teaching equipment in KOPEL, organizing workshops for academia-KOPEL members and so forth. This programme has rapidly gained much popularity amongst the local communities in the Kinabatangan District. Indirect spill-over effects of this programme to KOPEL include involvement of two agencies, the Sabah Department of Fisheries and Syarikat Akua Jaya Enterprise, in assisting the preparation of equipment and raw materials for the teaching modules.